Gender Profiling of ads in Egyptian Channel MBC - Al-Rawi, Bushra Jameel; Jabaar, Ranin (ALBAHITH ALALAMI, 2017)
The study begins with the idea that advertising is a form of culture. Therefore, it is not possible to be surrounded by an actual briefing from one-sided premises such as those that are based solely on the artistic, aesthetic or technical aspects, without linking it to the culture in which it is produced. The researcher attempts to shed light on the relation between the advertising letter and the concept of gender. And here lies the importance of the research as the content of the ads and their form and implicit values in the text and image reflect the cultural values that must be identified as well as the most important roles that are stereotyped in advertisements and their relationship to the culture of society. Advertising is an important factor in socialization in modern societies and is used as a tool to preserve some social structures such as gender. The differences are between man and woman in attitudes, behavior and social status is portrayed. These differences are gender-specific. The ads give viewers a glimpse of a world with social definitions, relationships, and gender roles. These images are developed to imitate the real life and many misconceptions of the imagination and reality in particular the ads. The problem lies in the issue of gender sterotyping in advertisement and how to shorten roles in a particular style. Gender stereotyping can be defined as a situation in which a person’s value is limited by his attractiveness or sexual behavior, which leads to the exclusion of his other characteristics and conversion to sexual use. People have to simplify the imperfections which may be limited to a certain form without paying attention to the myriad of other choices.